Sodium channel regulatory mechanisms : current fluctuation analysis on frog skin epithelium - Chou, Kuang-Yi (Division of Cell Biology, 2018)
This project examined the role of the cytoskeleton in regulatory mechanisms of the amiloride-sensitive Na⁺ channels in isolated frog skin epithelium. The epithelium from ventral frog skin is a model tissue which has proved significant in our understanding of the basic principles involved in water and Na⁺ homeostasis. In particular, this project examines ways in which local (non-hormonal) and hormonal regulatory mechanisms adjust the Na⁺ permeability of apical membranes of frog skin epithelium. Both mechanisms contain factors that are known to increase the apical membrane Na⁺ permeability mainly by increases in the number of open channels. The origin of these new open channels is unknown but, it is postulated that they could arise either by activation of quiescent channels already present in the apical membrane, or by recruitment of channels from cytoplasmic stores. Regarding the latter hypothesis, we also examined the idea that the cytoskeleton might somehow be involved in the insertion of Na⁺ channels within vesicles, into the apical membrane. This is based on the fact that the cytoskeleton is involved in a similar mechanism whereby, in the toad urinary bladder, anti-diuretic hormone (ADH) causes the insertion of aggregates with water channels. Much current interest focuses on the role of the cytoskeleton in the regulation of epithelial Na⁺ channels. To test this hypothesis, we used noise analysis to examine the effects of disrupting the cytoskeleton, on two different mechanisms which bring about changes in open channel densities. The mechanisms are: (1) lowering mucosal Na⁺ concentration (non-hormonal), and (2) addition of arginine-vasopressin (A VP) (hormonal). Non-hormonal, autoregulatory changes in apical membrane Na⁺ conductance were examined by investigating the effects of reducing the mucosal Na⁺ concentration. Our results showed that lowering the mucosal Na⁺ concentration induced large increases in the open channel density in order to stabilise the transport rate. In addition, we observed an average 55-60% increase in the open channel probability, which implies that in epithelium from Rana fuscigula, changes of channel open probability are also an important mechanism in the autoregulation of channel densities in response to a reduction in mucosal Na⁺. The hormonal control of Na⁺ channels by A VP has been intensively studied by noise analysis and the patch clamp. Our results confirmed previous reports that A VP increases the Na⁺ transport rate by increasing the number of open Na⁺ channels, primarily through large changes in the total number of channels, without a significant change in open probability. Regarding the role of the cytoskeleton in regulation of Na⁺ channels and/or its possible role in control of inserting putative vesicles with Na⁺ channels, we studied the effects of disrupting the cytoskeleton on the two regulatory mechanisms. Disrupting microtubules with colchicine had no, or very little effect on either of the regulatory mechanisms. On the other hand, the integrity of the microfilaments was very important for the autoregulatory changes in the number of open channels. After cytochalasin B treatment, lowering the mucosal Na⁺ concentration did not result in the usual compensatory changes in channel densities. There was no prior evidence that cytochalasin B had any actual effect on the F-actin network in the frog skin epithelium. Accordingly, modified cytochemical techniques were designed to demonstrate and localise F-actin in the epithelial granular cells. The direct immunofluorescent method proved useful, but did not allow sufficient resolution to examine the changes to different populations of actin in the cells. We then modified an immunogold method to suit our conditions, and the results demonstrated the localisation of different pools of F-actin and showed the effects of the cytochalasin B and vasopressin.